2021
DOI: 10.1016/j.cub.2021.01.065
|View full text |Cite
|
Sign up to set email alerts
|

The essential role of sodium bioenergetics and ATP homeostasis in the developmental transitions of a cyanobacterium

Abstract: Highlights d Synechocystis engages sodium bioenergetics during nitrogen starvation d Sodium-dependent ATP synthesis is only essential during metabolic dormancy d ATP levels are finely tuned according to the metabolic requirements

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Bis-(1,3-Dibutylbarbituric Acid)-trimethine oxonol (DiBAC4(3)) was used as described in ( Doello et al, 2021 ). 190 μL of cultures at timepoints 24 and 48 h after IPTG induction was stained for 30 min in the dark at RT with 10 μM DiBAC4(3) dissolved in dimethyl sulfoxide (DMSO).…”
Section: Methodsmentioning
confidence: 99%
“…Bis-(1,3-Dibutylbarbituric Acid)-trimethine oxonol (DiBAC4(3)) was used as described in ( Doello et al, 2021 ). 190 μL of cultures at timepoints 24 and 48 h after IPTG induction was stained for 30 min in the dark at RT with 10 μM DiBAC4(3) dissolved in dimethyl sulfoxide (DMSO).…”
Section: Methodsmentioning
confidence: 99%
“…To better understand the role of Na + energetics in energy metabolism, we investigated cell growth after adding either a Na + -specific ionophore monensin 19,20 , a protonophore DTHB 21 , or a typical F-type ATP synthase inhibitor DCCD 22 to the respective culture medium. If Na + fluxes were coupled to ATP synthesis, the collapse of the Na + transmembrane gradient caused by monensin should lead to growth arrest due to the inhibition of ATP synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Only recently, although not directly related to N 2 fixation, a study using Synechocystis sp. PCC 6803 reported that N-starved cells engage in Na + energetics for ATP synthesis for maintaining viability and to awaken from dormancy 20 . These reports suggest that Na + energetics may be more widespread in cyanobacteria than commonly thought.…”
Section: Discussionmentioning
confidence: 99%
“…Whether there is a metabolic connection between the hydrogenase and the Na + -ATPase remains to be investigated. In addition to a possible halotolerance function, nitrogen-starved cells of Synechocystis PCC 6803 use ATPase to produce a sodium motive force that maintains sufficient levels of ATP for survival during metabolic dormancy [ 56 ]. Both sodium bioenergetics and glycogen catabolism are important during the resumption of growth in Synechocystis PCC 6803 following nitrogen starvation [ 56 ], and future work could address if hydrogenase activity also contributes.…”
Section: Resultsmentioning
confidence: 99%